PEMANFAATAN CITRA LANDSAT 8 UNTUK PEMETAAN SEBARAN DAN KERAPATAN EKOSISTEM MANGROVE DI KECAMATAN CIJULANG KABUPATEN PANGANDARAN - Fakhra Annaba Piawai; Arry Sakti Al Faridzi Permana; Agung Mi'raj Fajar; Riki Ridwana; Lili Somantri (Universitas Negeri Padang, 2022)
The use of technology and methods in mapping continues to develop. Remote sensing images from the Landsat 8 satellite can be used for mapping mangrove vegetation. The advantages of mapping using remotely sensed imagery are that it is better in terms of time, cost, and effort, but the level of accuracy is quite small compared to terrestrial mapping. The purpose of this study was to determine the distribution and extent of mangrove vegetation in the administrative area of ​​Cijulang District, Pangandaran Regency. The composite used in this mapping is the RGB 563 composite in the Landsat 8 image because it is considered to highlight the different aspects of mangrove vegetation with non-mangrove vegetation. Classification of mangrove vegetation density classes using the Normalized Difference Vegetation Index (NDVI) and Modified Soil and Atmospheric Resistant Vegetation Index (MSARVI) methods which are divided into sparse, medium, and dense classes. It is known that the mangrove ecosystem in the Cijulang District, Pangandaran Regency is only found in Cijulang Village, Kondangjajar Village, and Batukaras Village. From the results of the calculation of the area of ​​​​the mangrove ecosystem in Cijulang District, Pangandaran Regency, it is about 260 hectares